(untitled) - Tropp, Burton E. (Burlington, Mass, 2014)
Includes access to the Student Companion Website with every print copy of the text. Written for the more concise course, Principles of Molecular Biology is modeled after Burton Tropp's successful Molecular Biology: Genes to Proteins and is appropriate for the sophomore level course. The author begins with an introduction to molecular biology, discussing what it is and how it relates to applications in "real life" with examples pulled from medicine and industry.
Keywords: Biochemical Phenomena.,Genes,Proteins,Đạm,Gen,Sinh học hóa học.; Physiology,Physiology,Sinh lý học,Sinh lý học